Indonesian adaptation and validation of the Social Media Competence Scale for College Students (SMC-CS): A confirmatory factor analysis approach - Fadhil Maliky Islah; Julaibib (Universitas Mercu Buana Yogyakarta, 2025)
The rapid integration of social media into students’ academic, social, and personal lives underscores the need for valid and reliable instruments to assess social media competence. Understanding this competence is crucial, as social media is not only a communication tool but also a source of information, a space for self-expression, and a domain for identity formation. This study aimed to adapt and validate the Social Media Competence Scale for College Students (SMC-CS) into Bahasa Indonesia. The adaptation process followed standardized cross-cultural procedures, including translation, expert review for content validity, conceptual alignment, and pilot testing. A total of 728 university students aged 17–25 years from various Indonesian institutions participated in this study. Data analysis was conducted using Confirmatory Factor Analysis (CFA) with the MLM estimator to address multivariate non-normality. The Indonesian version of the SMC-CS demonstrated a four-factor structure—Technical Usability, Content Interpretation, Content Generation, and Affective Regulation—with strong reliability (CR > 0.83) and acceptable convergent validity (AVE ≥ 0.47). These findings provide evidence that the adapted instrument is both valid and reliable for assessing college students’ social media competence in the Indonesian context. Keywords: College students, confirmatory factor analysis, cross-cultural adaptation, social media competence scale.